Purification of antibodies against hepatitis B. - Ling, Tau Chuan; Wongchupan, Rattana; Tan, Wen Siang; Taip, Farah Saleena (2010)

(untitled)
The present invention discloses a method for the purification of polyclonal immunoglobin G (IgG) against type B hepatitis infections, the method comprising the steps of: (i) adsorption of serum on diethylaminoethyl (DEAE) sepharose without elution, in which albumin content in the serum is removed: and (ii) adsorption of the albumin depleted serum on an immobilized dye followed by elution, in which the adsorbed antibodies are eluted in pure form.